An Investigation of Behavioural and Self-Reported Cognitive Empathy Deficits in Adolescents With Autism Spectrum Disorders and Adolescents With Behavioural Difficulties - Vilas, Sara P.; Reniers, Renate L. E. P.; Ludlow, Amanda K. (Frontiers in Psychiatry, 2021)
Deficits in empathy have been considered hallmarks in individuals with autism spectrum disorders (ASD) but are also considered to underlie antisocial behaviour associated with individuals with callous unemotional traits (CU). Research has suggested that individuals with autism spectrum disorders show more difficulties with cognitive empathy, and that individuals diagnosed with behaviours difficulties, characterised by CU traits and antisocial behaviour, demonstrate low affective empathy. In the current manuscript we present findings of two studies. The first study describes the validation of a new stimulus set developed for the empathic accuracy task. The second study compares the performance of 27 adolescents with ASD, 27 age matched typically developing adolescents and 17 adolescents with behavioural difficulties on the empathic accuracy task and a self-report measure of empathy. The adolescents with ASD and CD showed deficits in their cognitive empathy only across the self-report measures. Adolescents with ASD showed lower scores in particularly their perspective taking abilities, whereas the adolescences with behavioural difficulties showed more difficulties with their online simulation. No differences in affective empathy across the three groups were observed. Clinical implications of the findings are discussed.